2004
DOI: 10.1177/0885066604263828
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Experience With Nesiritide in the Pediatric Population

Abstract: Nesiritide is a recombinant formulation of brain-type natriuretic factor. Preliminary experience in the adult population suggests that nesiritide may be an effective agent in the treatment of decompensated congestive heart failure. Given its physiologic effects, it may be an effective agent in the pediatric population; however, to date, there are no reports regarding its use in infants and children. The authors retrospectively review their experience with nesiritide in 5 pediatric patients. The cohort of 5 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Marshall et al (7) reported the use of nesiritide in five pediatric patients, two of whom had previously undergone heart surgery. The authors suggested that the medication was well tolerated, although given the relatively small study population, analysis of beneficial hemodynamic effects was limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marshall et al (7) reported the use of nesiritide in five pediatric patients, two of whom had previously undergone heart surgery. The authors suggested that the medication was well tolerated, although given the relatively small study population, analysis of beneficial hemodynamic effects was limited.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are limited data regarding the use of nesiritide in children with low cardiac output and CHF (7). Previous studies have demonstrated that low cardiac output is common after congenital heart surgery and is characterized by elevated filling pressures and impaired organ perfusion (8,9).…”
mentioning
confidence: 99%
“…Clinically, these variables are of interest primarily in relation to their effect on cardiac output. To date only one group has attempted to assay the effect of nesiritide on cardiac output, and they did so in a small group of patients (n 05) using qualitative clinical measures [10]. Studies with more precise assays are necessary to determine if nesiritide improves cardiac output in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Other agents, such as nesiritide (recombinant B-type natriuretic peptide), have been tested in adults with AKI, but they have shown no impact on urine output, glomerular filtration rate, or need for RRT; however, these data are not necessarily applicable to pediatric patients. 22,23 Fenoldopam might improve urine output in pediatric AKI, but it has no effect on serum creatinine level. 24 These interventions might have a greater beneficial effect on AKI if they are initiated early in the disease course, the timing of which could be measured by increases in the levels of biomarkers of AKI.…”
Section: Conservative Therapymentioning
confidence: 99%